Reasons for prescription opioid use while playing in the National Football League as risk factors for current use and misuse among former players - Dunne, Eugene M. (Clin J Sport Med, 2020)
OBJECTIVE: Prescription opioid misuse has become a significant public health issue. Previous research has examined predictors of prescription opioid use and misuse among former National Football League (NFL) players. The present study aimed to describe how reasons for prescription opioid use while in the NFL corresponds to use and misuse in retirement. DESIGN: Former NFL players reporting prescription opioid use during their playing careers (N = 336) were included in this secondary data analysis. Participants reported reasons for prescription opioid use, including pain management, use “to function”, to improve mood, to reduce stress, and to aid sleep. RESULTS: Among retired NFL players with exposure to prescribed pain medication during their playing career, 26.2% reported recent use of prescription opioids (past 30 days) and 73.8% reported no use. Specifically, 14.3% of retired players reported opioid use only as prescribed, while 11.9% reported misuse (not prescribed or use other than as prescribed). Using prescription opioids to function while in the NFL was associated with any opioid use in the past 30 days (OR = 1.30, 95% CI: 1.12, 1.50, p < .001). Further, opioid use in the NFL to reduce stress and anxiety was associated with increased odds of past 30-day misuse of prescription opioids (OR = 1.45, 95% CI: 1.01, 2.11; p = .048). CONCLUSIONS: The present study adds to the literature on elite athletes at high-risk for pain and prescription opioid use and misuse. The findings may help to identify and provide early intervention for professional athletes most at risk for misuse of prescription opioids.